Functional relevance of G-protein-coupled-receptor-associated proteins, exemplified by receptor-activity-modifying proteins (RAMPs). (August 2002) - Fischer, J. A.; Muff, R.; Born, W.
Abstract : The calcitonin (CT) receptor (CTR) and the CTR-like receptor (CRLR) are close relatives within the type II family of G-protein-coupled receptors, demonstrating sequence identity of 50%. Unlike the interaction between CT and CTR, receptors for the related hormones and neuropeptides amylin, CT-gene-related peptide (CGRP) and adrenomedullin (AM) require one of three accessory receptor-activity-modifying proteins (RAMPs) for ligand recognition. An amylin/CGRP receptor is revealed when CTR is co-expressed with RAMP1. When complexed with RAMP3, CTR interacts with amylin alone. CRLR, initially classed as an orphan receptor, is a CGRP receptor when co-expressed with RAMP1. The same receptor is specific for AM in the presence of RAMP2. Together with human RAMP3, CRLR defines an AM receptor, and with mouse RAMP3 it is a low-affinity CGRP/AM receptor. CTR-RAMP1, antagonized preferentially by salmon CT-(8–32) and not by CGRP-(8–37), and CRLR-RAMP1, antagonized by CGRP-(8–37), are two CGRP receptor isotypes. Thus amylin and CGRP interact specifically with heterodimeric complexes between CTR and RAMP1 or RAMP3, and CGRP and AM interact with complexes between CRLR and RAMP1, RAMP2 or RAMP3.